Radical markets by Eric posner and E glen Weyl: A review essay* - Levine, David (Journal of Economic Literature)
At a time when standards of living have improved more than any time in history, this book makes a proposal for radical change. It is based$1 (Bloosely$1 (Bon market design principles. The plan for attacking overlapping ownership is reasonably well thought out. Most of the book, however, proposes to use mechanisms designed for a narrow purpose; to attack real or imagined problems that they are ill-suited to solve. I conclude that while market design has a lot to offer when properly applied, the proposals here are not sufficiently well thought out to constitute a serious plan of action.- Reproduced s
Keywords: Market design principles